Foraminíferos planctônicos do Paleoceno no testemunho DSDP site 356, platô de São Paulo, Atlântico Sul: bioestratigrafia e inferências paleoecológicas - Krahl, Guilherme (Universidade do Vale do Rio dos Sinos, 2016)
The Paleocene is characterized by an interval that succeeds the K-Pg mass extinction event which affected several fossil groups. In its study reveals not only a sequential pattern of evolutionary radiation but also processes related to the complex recovery of marine ecosystems. Due to their ecological characteristics the planktonic foraminifera are an important paleoceanographic tool for the understanding of the physicochemical evolution of marine pelagic systems as well as the evolution of the group along the Paleocene. In this context, this paper aims to conduct a biostratigraphic and paleoecological analysis based on Paleogene planktonic foraminifera assemblages (Danian/Seladriano) from the DSDP Site 356 (Leg 39) drilled in the western South Atlantic.
Keywords: Foraminíferos planctônicos; Paleoceno; Bioestratigrafia; Paleoecologia; Planktonic foraminifera; Paleocene; Bioestratigraphy; Paleoecology; ACCNPQ::Ciências Exatas e da Terra::Geologia